2018
DOI: 10.17576/mjas-2018-2201-11
|View full text |Cite
|
Sign up to set email alerts
|

EFFECT OF EXTRACTION METHODS ON THE YIELD, FUCOSE CONTENT AND PURITY OF FUCOIDAN FROM Sargassum sp. OBTAINED FROM PULAU LANGKAWI, MALAYSIA

Abstract: The objective of this study was to determine the effect of extraction methods on the yield, fucose content and purity of fucoidan that had been isolated from brown seaweed, Sargassum sp. The extraction of fucoidan was carried out based on the factorial design assigned, which involved three different parameters including two types of extraction (acid and alkaline), three different extraction temperatures (45, 65 and 85 °C) and three different extraction time (1, 3 and 5 hours). Results obtained showed that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 15 publications
0
1
0
1
Order By: Relevance
“…Studies have reported that fucose content varies among seaweeds species, extraction techniques [37], extraction [46], harvest time [51,61], plant part [38], and maturity of the seaweed [37], and it was suggested that the higher amount of fucose may contribute to the higher cytotoxic activity of algal PS [62]. The average fucose content obtained in this research was 31.68% and 11.19% for F. virsoides and C. barbata, respectively.…”
Section: Influence Of Algal Species Solvent and Extraction Technique ...mentioning
confidence: 49%
See 2 more Smart Citations
“…Studies have reported that fucose content varies among seaweeds species, extraction techniques [37], extraction [46], harvest time [51,61], plant part [38], and maturity of the seaweed [37], and it was suggested that the higher amount of fucose may contribute to the higher cytotoxic activity of algal PS [62]. The average fucose content obtained in this research was 31.68% and 11.19% for F. virsoides and C. barbata, respectively.…”
Section: Influence Of Algal Species Solvent and Extraction Technique ...mentioning
confidence: 49%
“…Average crude %PS from F. virsoides was 9.75% and from C. barbata 8.86%. Although both of these seaweeds are order Fucales, PS% highly depended on seaweed species, and within the same species it is also influenced by several other factors, such as extraction procedure and solvent, harvest season, and geographic location as well as the maturity of the plant [36,37]. Usov et al [38] reported that %PS from 25 different brown seaweed species ranged between 0.4% and 20.4%, while in the study of Turan et al [39] they constituted up to 25-30%.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, fucoidan was extracted from S. polycystum with a ratio of 4.51 ± 0.24% and contained 38.76 ± 0.26%, 22.35 ± 0.23%, 3.9 ± 1.8%, and 4.7 ± 0.43% of carbohydrate, sulphate, uronic acid and protein, respectively (Palanisamy et al, 2017). Extraction method, seaweed harvesting season, location, and level of maturation may all influence fucoidan yield and chemical composition (Rani et al, 2017;Baba et al, 2018). Recently, Tsou et al, has extracted fucoidan samples at two temperatures (65 and 80°C) from Sargassum ilicifolium collected from five different locations in southern Taiwan and confirmed that location and temperature of extraction can significantly influence the yield (1.47%-2,73%) and the chemical composition of fucoidan (Tsou et al, 2022).…”
Section: Extractionmentioning
confidence: 99%
“…Desde el descubrimiento de la estructura molecular del fucoidan por Kylin en 1913, otras estructuras de fucanos de diferentes algas pardas han sido investigadas considerando su distribución en el tejido algal y la divergencia estructural (Morya et al 2012). Se ha estudiado el contenido de fucoidanos en las algas pardas Adenocystis utricularis, Analipus japonicus, Ascophyllum nodosum, Bifurcaria bifurcate, Chorda filum, Cladosiphon okamuranus, Cystoseira indica, Dictyota menstrualis, Ecklonia kurome, Fucus distichus, Fucus evanescens, Fucus serratus, Fucus vesiculosus, Himanthalia lorea, Hizikia fusiforme, Kjellmaniella crassifolia, Laminaria saccharina, Laminaria digitata, Fucus spiralis, Laminaria cichorioides, Laminaria religiosa, Laminaria japonica, Laminaria angustata, Lessonia vadosa, Lobophora variegate, Macrocytis pyrifera, Padina pavonia, Padina gymnospora, Pelvetia canaliculata, Pelvetia wrightii, Saccharina latissima, Sargassum linfolium, Sargassum sp., Sargassum stenophyllum, Spatoglossum schroederi, Stichopus japonicas, Stoechospermum marginatum, Undaria pinnatifida entre otras (Ale et al 2011, Morya et al 2012, Rani et al 2017, Baba et al 2018.…”
Section: Introductionunclassified